Doppler evaluation of umbilical artery during normal gestation in sheep. (22nd August 2018) - Troisi, Alessandro; Cardinali, Lucia; Orlandi, Riccardo; Menchetti, Laura; Robiteau, Guillaume; Polisca, Angela
Contents: Throughout gestation, changes in foetal umbilical cord Doppler parameters in ewes were detected. Doppler ultrasonography of the umbilical artery was performed weekly starting at 18 weeks before parturition until birth. In the foetal umbilical artery (UA), systolic peak velocity (SPV), end diastolic velocity (EDV), increased ( p for within‐subjects effect <0.001) while pulsatility index (PI) resistance index (RI) decreased ( p for within‐subjects effect <0.001) with the progress of pregnancy. A linear trend was found on all patterns ( p < 0.001). In particular, the EDV values increased significantly ( p < 0.05) with respect to previous weeks, at weeks 16, 11, 10, 7, and 1 before parturition. The SPV values increased significantly ( p < 0.05), with respect to previous observations, at weeks 11, 10, and 7 before parturition. Finally, the PI and RI decreased significantly ( p < 0.05) only at week 7 before parturition. The increased velocities and reduced resistance index suggest a progressive increment in blood flow to the foetus towards the end of pregnancy. Foetal and utero‐placental vascular parameters can be reliably evaluated using high‐frequency ultrasound.